Impact of Modernisation in Mamang Dai’s The Legends of Pensam - Nilofer A; Maheswari, Uma (International Journal of Psychosocial Rehabilitation, 2020)
The research article “Impact of Modernisation in Mamang Dai’s The Legends of Pensam” emphasizes the need for consideration of the tribal cultures that are fading from the face of the earth. The study expounds the significance of knowing the rationales behind the misconceptions against the tribal societies who are hardly recognized as an integral part of the globe. The tribal communities in India are losing their traditional cultures due to the growing modernisation that followed colonialism. The challenges confronted by the tribes of the northeast particularly the Adis of Arunachal Pradesh during the colonial and the postcolonial epochs are accentuated in this study. The lives of the tribal and the indigenous communities are made vulnerable and the stance of Dai is highlighted in the study through the concept of postdevelopmentalism that has some consideration for the fourth world people.